MgSO4 And Slow Stroke Back Massage Therapy On Blood Pressure of Severe Pre Eclampsia Pregnant Women - Nikmah, Ulin; Machmudah, Machmudah (University of Muhammadiyah Semarang, 2019)
Preeclampsia is a dangerous complication for pregnant women and their fetuses, this can cause damage to body organs namely heart failure, kidney failure, liver dysfunction, blood clotting disorders, death for the mother and fetus, if not immediately addressed well and correctly. Management of severe preeclampsia by administering MgSO4 intravenously to mothers as prevention of seizures, one of the nursing actions to overcome preeclampsia patients is the provision of relaxation techniques Slow stroke back massage. The objective of this research to determine the effectiveness of MgSO4 Therapy and Slow Stroke Back Massage on Blood Pressure Response In Severe Preeclampsia Pregnant Women at Roemani Hospital Muhammadiyah Semarang. This research uses the quasi-experimental design with the pre and post test perspective. This research measured 32 the pregnant women with severe preeclampsia at Roemani Muhammadiyah Hospital Semarang from purposive sampling technique. The result of this research was shown the effect of blood pressure reduction in all preeclampsia pregnant women given MgSO4 therapy and slow stroke back massage. There is a significant influence on the provision of MgSO4 therapy and slow stroke back massage on the blood pressure response of severe preeclampsia pregnant women.